The New Method of Searching Cut-Sets in the System Reliability Analysis of Plane Steel Trusses - Katarzyna Kubicka (Applied Sciences, 2022)
This paper focuses on the new method of searching cut-sets, which enables us to conduct the system reliability analysis for plane trusses. As the result of such, the analysis of the reliability index for the whole structure is obtained, not only for the single elements. In the case of truss structures, the huge number of cut-sets could be generated if only the geometry of the structure is taken into account. Considering also the effects of actions and the load capacity, it is possible to reduce the number of cut-sets: what makes the whole analysis faster and more effective. The structures were considered not only in persistent design situations, but also in accidental-under-fire influence. The effect of action in individual elements was computed using the Robot Structural Analysis program. The temperature of the elements under fire load and the load-bearing capacity of the elements were calculated according to the Eurocode procedure in the Mathematica script. The proposed method allows to reduce the number of cut-sets, what makes the whole procedure of system reliability analysis much more efficient. All cut-sets were found by using a C++ console application prepared by author.